Answer:
3
Step-by-step explanation:
because its is like subtacting
Answer:
R=10
Step-by-step explanation:
-2×-3=6
R=5×2
=10
We can solve these equations by using substitution method where you substitute one equation to the other and solve for the value of the other variable. We do as follows:
y = 2x^2
y = –3x −1
2x^2 = –3x −1
2x^2 +3x +1 = 0
x1= -0.5
x2 = -1
y1 = 0.5
y2 = 2
Answer:
4x2y2−12y
Step-by-step explanation:
Write the problem as a mathematical expression. ( x y 2 x − 3 y ) ⋅ 4 Multiply x by x by adding the exponents. ( x 2 y 2 − 3 y ) ⋅ 4 Simplify by multiplying through. 4 ⋅ ( x 2 y 2 ) − 12 y Remove parentheses. 4 x 2 y 2 − 12 y